2013
DOI: 10.1097/adt.0b013e31827d8763
|View full text |Cite
|
Sign up to set email alerts
|

Early Maladaptive Schemas and Substance Use

Abstract: Substance abuse disorders continue to be problematic in society and remain a serious health problem. Existing treatment approaches provide benefits, although many individuals do not respond to treatment or experience relapse. Schema therapy represents an alternative treatment approach for which there is mounting evidence, particularly in relation to the existence of early maladaptive schemas (EMSs) and their role in psychopathology. The current study assessed EMS and substance use in a nonclinical sample. EMSs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
(18 reference statements)
0
1
0
1
Order By: Relevance
“…[7][8][9] Literature suggests that addressing maladaptive schemas may improve substance use outcomes because of their integrity with personality structure and underlying impact on substance use. [10][11][12] Dual focus schema therapy (DFST) was developed by Ball 11,12 to modify EMSs among chronic substance users with comorbid personality disorders. DFST is a six-month-long treatment that integrates strategies from schema therapy 6 and relapse prevention.…”
Section: Original Articlementioning
confidence: 99%
“…[7][8][9] Literature suggests that addressing maladaptive schemas may improve substance use outcomes because of their integrity with personality structure and underlying impact on substance use. [10][11][12] Dual focus schema therapy (DFST) was developed by Ball 11,12 to modify EMSs among chronic substance users with comorbid personality disorders. DFST is a six-month-long treatment that integrates strategies from schema therapy 6 and relapse prevention.…”
Section: Original Articlementioning
confidence: 99%
“…Research in the field of 'affective structure' has consistently identified two dominant dimensions (Pourferj Omran et al, 2016). In this context, a two-factor model of affect has been presented, named 'positive affect' and 'negative affect' (Aaron, 2013). Positive and negative affect refers to the extent to which a person feels pleased and happy, or displeased and unhappy.…”
Section: Introductionmentioning
confidence: 99%
“…Various researches have shown that factors of success and achievement in individuals stem from the positive emotions and feelings they generate. Conversely, unsuccessful individuals are those who cultivate negative emotions and feelings within themselves (Aaron, 2013). Positive affect indicates enjoyable interactions of a person with the environment, leading to feelings of activeness and eagerness.…”
Section: Introductionmentioning
confidence: 99%
“…Tal rigidez perpetua indefinidamente o ciclo vicioso: consumo -faltaconsumo (Rocha & Junior, 2010). (Aaron, 2013;Díaz et al, 2011;Shorey et al 2012d;2013b; 2013d), além de diferenças significativas quando comparadas aos escores de amostras não clínicas (Jalali et al, 2011;Shorey et al 2012b;Silva et al, 2012). Resultados de outras pesquisas, ainda, apresentaram correlação significativa entre o uso de substâncias e o domínio Desconexão e Rejeição (Aaron, 2013;Díaz et al, 2011;Shorey et al 2013a) e seu poder em predizer o potencial para adicção (Bojed & Nikmanesh, 2013).…”
Section: Médias De Respostas Dos Eids Na Amostraunclassified